Editorial (Management and Connections Journal, 2013)
DOI: http://dx.doi.org/10.13071/regec.2317-5087.2013.2.2.5955.5-8Presents the second issue of the Management and Connections Journal (Revista Gestão & Conexões), v2, n2, jul./dec. 2013.